KOREAN AND POLISH CLAUSES OF LEASE OBJECTS IN TRANSLATION - WOJTASIK, Emilia (Comparative Legilinguistics, 2014)
The article focuses on a preliminary comparative analysis of clauses of lease objects in civil contracts of Korean and Polish law. The research methods include Kierzkowska’s pragmatic translation model (2002) as well as Vermeer’s model of skopos and the comparison parallel texts. The analysis is preceded by a short introduction on the legal systems of the Republic of Poland and the Republic of South Korea, presented as a kind of compromise worked out in the need to reconcile tradition and meeting the requirements of globalization along with the progress of civilization. The main part of the article analyzes the translation of the lease object clause in the lease contract, starting from its description and characteristics of the contract objects through pointing out the terms and conditions of transfer or return of the lease object to the tenant. The article aims at pointing presenting the analysis of legal language used in the pertinent contract clause in translation context. It also presents grammatical and lexical issues typical in Polish- Korean translation.